Systematic Review of the Effects of Phosphodiesterase-5 Inhibitors and Dexamethasone on High Altitude Pulmonary Edema (HAPE) - Bliss, Amy (Spartan Med Res J, 2019)
OBJECTIVE: To review and synthesize the current available evidence of the effects of phosphodiesterase-5 inhibitors and dexamethasone on the outcomes of individuals affected by acute mountain sickness symptoms and High Altitude Pulmonary Edema (HAPE). METHODS: In 2015, two authors independently performed separate searches using three different databases (PubMed, Ovid and Web of Science) later reviewed by the third author. The searches used the following terms “High Altitude Pulmonary Edema” and “Phosphodiesterase-5 Inhibitors” while the second search used “High Altitude Pulmonary Edema” and “Dexamethasone”. The following exclusion criteria were utilized: patients < 18 years old, non-human studies, studies at altitudes < 2,000 meters. The search included articles from year 2000 to current. RESULTS: A total of 237 manuscripts were initially reviewed. The search involving phosphodiesterase-5 inhibitors initially yielded 37 manuscripts, four of which met inclusion criteria. A total of 101 patients were included in these articles. For the Dexamethasone search, 200 manuscripts were retrieved. Three of these studies met the inclusion criteria, reporting data on a total of 66 patients. None of the studies reported significant improvements in outcomes of patients from the use of either phosphodiesterase-5 inhibitors or dexamethasone. CONCLUSIONS: According to the current available literature, neither phosphodiesterase -5 inhibitors or dexamethasone significantly alter the outcome of individuals affected by HAPE.